(untitled) (Zaporizhzhia Historical Review, 2021)
On the basis of the new archival sources involvement the article demonstrates the administrative - censorial oppressions of legal periodical editions of Ukrainian political parties of Naddniprianschina as well as the peculiarities of their application during the years of the 1st Russian Revolution (1905-1907)